Relationship between time management in construction industry and project management performance - Nasir, Najuwa; Mohd Nawi, Mohd Nasrun; Radzuan, Kamaruddin (2016)
Nowadays, construction industry particularly in Malaysia struggle in achieving status of eminent time management for construction project.Project managers have a great responsibility to keep the project success under time of project completion. However, studies shows that delays especially in Malaysian construction industry still unresolved due to weakness in managing the project.In addition, quality of time management on construction projects is generally poor.Due to the progressively extended delays issue, time performance becomes an important subject to be explored to investigate delay factors.The method of this study is review of literature towards issues in construction industry which affecting time performance of project in general by focusing towards process involved for project management. Based on study, it was found that knowledge, commitment, cooperation are the main criteria as an overall to manage the project into a smooth process during project execution until completion. It can be concluded that, the strength between project manager and team members in these main criteria while conducting the project towards good time performance is highly needed.However, there is lack of establishment towards factors of poor time performance which strongly related with project management.Hence, this study has been conducted to establish factors of poor time performance and its relations with project management.